Redução da emissão de CO2 de lajes mistas de aço e concreto via algoritmos metaheurísticos - Teixeira, Mariana Oliveira (2023)
Steel and concrete composite slabs are structural elements that stand out for their advantages, such as the possibility of construction without shoring, ease of installation, construction speed and reduction of tensile reinforcement in regions of positive moment. However, it is noted that in practice this system still has unexplored potential, such as, for example, not considering of continuity of composite slabs under the supports and not considering additional positive tensile reinforcement to the steel formwork. In addition, as civil construction is one of the main responsible for the emission of CO2 into the atmosphere, researches that seek less polluting structural solutions to the environment are necessary. In this context, this research looking for to present the optimal structural solution, with the lowest CO2 emissions, for the construction of composite steel and concrete slabs, considering simply-supported and continuous spans and the dimensioning in the composite phase. A computer program was developed in the MATLAB® numerical computation and programming platform for the analysis and dimensioning of composite slabs according to ABNT NBR 8800:2008. For the structural optimization, the Particle Swarm and Gray Wolf Algorithms were used. The tool was rightly validated and an analysis of simply-supported and continuous composite slabs composed of three different steel formwork available on the market, varying the thickness of the concrete layer, the thickness of the formwork, the compressive strength of the concrete and the diameter of the tensile reinforcement in the positive and negative moment regions was performed. The results indicate that, when comparing the optimal solutions with those provided by the manufacturers, emissions can be reduced by up to 40% and that the simply-supporting slabs are more efficient than the continuous slabs from an environmental point of view. Additionally, it was verified that the insertion of additional positive reinforcement reduces the emission of CO2 from the slab, as it reduces the consumption of steel in the formwork, which is the material responsible for most of the emissions.